English Teachers’ Perceptions on Using Media Social in Teaching English - Nazriani Lubis; Siti Rahmadiah (Indonesian Journal of ELT and Applied Linguistics, 2022)
Social media in learning Englsh is now used by people who have many functions,one whih can be used as a medium for language learning. Social media are effective learning media to assist the learning and teaching process. The use of media in learning English in Junior High School is able to make students do more Learning activities,and other activies such as observing,doing,demonstrating and so on. It was found teachers had positive perceptions of technologies.thematic analysis is the process of identifying and analyzing pattern or themes in qualitative. Based on the research result,teacher perceptions tend to be quite positive about the implementation of the teaching and learning process using media social. The tendency for perception is enthusiastic in taching media social as a tool to support the teaching and learning process at the school.